2020
DOI: 10.1017/inp.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

The effects of treatment and management history on the control of Old World climbing fern (Lygodium microphyllum), Brazilian pepper (Schinus terebinthifolia), and punktree (Melaleuca quinquenervia)

Abstract: To successfully reduce overall invasive plant cover over time, an effective treatment plan must be established such that mortality exceeds new colonization and re-spouting growth rates. However, few evaluations of the effects of long-term, consistent treatment at different intervals exist. We report the effects of treatment intensity on Old World climbing fern (Lygodium microphyllum (Cav.) R. Br.), Brazilian pepper (Schinus terebinthifolia Raddi) and punktree (Melaleuca quinquenervia (Cav.) S. T. Blake), as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have also shown that herbicide treatment after fire greatly reduces climbing fern coverage (Hutchinson 2010;Stocker et al 2008). Finally, recent field research has indicated that a treatment return interval of less than two years is needed to reduce Old World climbing fern (Dietz et al 2020).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Studies have also shown that herbicide treatment after fire greatly reduces climbing fern coverage (Hutchinson 2010;Stocker et al 2008). Finally, recent field research has indicated that a treatment return interval of less than two years is needed to reduce Old World climbing fern (Dietz et al 2020).…”
Section: Management Implicationsmentioning
confidence: 99%